Efektivitas Alat Sikat Gigi Otomatis Wall Mounted untuk Disabilitas pada SLB di Jember terhadap Indeks Kebersihan Mulut - Arina Rosyida; Kiswaluyo Kiswaluyo; Surartono Dwiatmoko (Pustaka Kesehatan, 2020)
Disability is a person with disabilities who has physical, mental, intellectual, sensory, and some motor disorders. Disabilities that have motor impairments are blind, mentally retarded, and disabled so they need an automatic wall-mounted toothbrush in cleaning teeth and mouth. A wall-mounted toothbrush is an innovative tool for blind, mentally disabled, and disabled people to be able to brush their teeth independently. The aim is to determine the effectiveness of automatic wall-mounted toothbrushes in children with disabilities, especially in the visually impaired, mentally retarded, and disabled. The study was conducted by pre-experimental method (One Group Pretest-Posttest Design) in SLB disabled people in Jember with 56 people, 17 people with visual impairment, 36 mental retardations, and 3 disabled people. The results of the study carried out a paired sample t-test showed a significance value (p <0.05) in the blind and mentally retarded while the significance value (p> 0.05) in the disabled. The conclusion of the study is that this tool is effective in the blind and mentally retarded but is less effective in the disabled.